The influence of imports, foreign exchange reserves, external debt, and interest rates on the currency exchange rates against the United States Dollar in Southeast Asia Countries - Rahma Nurjanah; Candra Mustika (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
This study aims to analyze the effect of imports, foreign exchange reserves, foreign debt, and interest rates on the currency exchange rates against the United States Dollar in Southeast Asia countries. The study results found that from 2010 to 2017, the currency exchange rates against the United States Dollar in Southeast Asian countries tended to weaken (depreciate).  The highest growth in the exchange rate against the United States dollar was in Indonesia, while the lowest was in Singapore. Foreign exchange reserves negatively affect foreign debt, and imports positively affect countries' exchange rates in the Southeast Asia region against the United States dollar. On the other hand, interest rates do not show a significant effect.